Effects of wolf predation risk on community weighted mean plant traits in Białowieża Primeval Forest, Poland - Lescinskaite, Jone (2018)
It is still largely unknown what effect does wolf risk have on the lower trophic levels in Europe. In the last European lowland forest these interactions were explored with a main browser species – red deer (Cervus elaphus), and other four less common ungulate species, one of which is European bison (Bison bonasus). To explore the effect of risk I use community-averaged and species-specific plant traits as indicators in regenerating tree communities. Browsing intensity and several functional plant traits were related to relative wolf (Canis lupus) encounter risk, red deer and other ungulate biomasses, and horizontal visibility factors. Browsing intensity did not decrease even in the areas where wolf encounter rate is high and red deer biomass is low. Evidence points out that bison could be as important browser in a deciduous mixed forest as red deer is. The full height of saplings and the height of the first branch mainly depended on red deer biomass. The height of the fork and branching index related more to other ungulate biomass and horizontal visibility. While coexisting in the same forest but on the opposite ends of wolf predation risk, the two browsers may be important top-down drivers within the system.